(untitled) (Research, Society and Development, 2022)
The objective of this research was to evaluate the configuration of costs and expenses evidenced in the financial statements for the years 2018 to 2021 of football clubs, being converted into unit values by the points obtained by the clubs according to the CBF ranking. Based on qualitative and quantitative research and document analysis, the financial statements of 42 clubs were analyzed. The results show a large variation between the minimum and maximum unit values, derived from the concentration of resources by a portion of Serie A clubs, while teams from the other series have lower unit and total values. Based on the results of the Chi-square test, it was possible to infer that the series in which the club is operating is related to the unit values of net revenue, and additionally, that the series in which the club is operating is not related to the separation of costs and expenses.